Experimental and Finite Element Study on 7A04 Aluminum Alloy Tube Confined High Strength Concrete Long Column - Zuo-Jin Zhang; Feng-Xia Han; Qing Liu (Geofluids)
7A04 aluminum alloy has high strength and strong corrosion resistance, and its quality is only 1/3 of steel. Using 7A04 aluminum alloy to replace ordinary steel tube to confined concrete, it can effectively reduce the member section, reduce the weight of the structure, and more in line with the material requirements of large span materials and high-rise buildings. In this paper, nine groups of 7A04 aluminum alloy tube confined high strength concrete long column were tested under axial compression and eccentric compression with aspect ratio and eccentricity as variables. And the corresponding ABAQUS finite element model was established. The results show that the failure phenomena of the nine groups are basically the same, and the specimen deflection curve shape is similar to the sine half-wave curve. The ultimate bearing capacity of the specimen decreases with the increase of aspect ratio and eccentricity. When the axial compression or eccentricity of the specimen is small, the variation of the longitudinal and transverse strain at the midspan is similar in the elastic stage. When the eccentricity is large, the longitudinal and transverse strain at the midspan of the specimen is obviously tensile at one side and compressive at one side at the beginning. Finally, based on the test and simulation results, a formula for calculating the bearing capacity of 7A04 aluminum alloy tube high strength concrete long columns is proposed. This formula can better predict the stable bearing capacity of the specimen, which has certain reference significance for the structural design of 7A04 aluminum alloy tube high strength concrete long columns.